(3GdeMGSHI GdeGdjI (B1 s (3OQhS h CeKdI h JeGQjf eMdhdI s - (3eQhT(B, (3jhSa s ((3GdLRGFQs (3OGQGdCLjGd GdQbejs, 2023)
(3GdeMGSHI gj dZI GdCYeGd, agj fXGe dJSLjd hJdNjU hJMdjd GdeYGedGJ GdeGdjI ddeDSSI(B. (3JSGYO GdeMGSHI aj GJNGP GdbQGQGJ hJbjje GdCOGA GdeGdj hEYOGO GdJbGQjQ GdeGdjI dCUMGH GdeUdMI, GdCUhd(B: (3ehGQO GbJUGOjI JedcgG GdeDSSI eKd GdfbO hGdMSGHGJ GdeOjfI hGdeNRhf hGdeeJdcGJ(B. (3GdNUhe, GdJRGeGJ eGdjI Ydi GdeDSSI eKd GdbQhV hGdMSGHGJ GdOGFfI(B.(3,Mbhb GdedcjI(B: (3MUI GdeGdcjf aj CUhd GdeDSSI HYO NUe GdNUhe(B.(3GdEjQGOGJ(B: (3JOabGJ fbOjI fGJLI Yf HjY GdefJLGJ Ch GdNOeGJ(B.(3, GdeUQhaGJ gj JcGdja GSJNOGe GdehGQO dJMbjb GdEjQGOGJs
Keywords: (3GdeMGSHI GdJMdjdjIs; (3GdejRGfjI GdYehejIs